1996
DOI: 10.1002/(sici)1520-6661(199609/10)5:5<281::aid-mfm6>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Fetal alloimmune thrombocytopenia: Consensus and controversy

Abstract: Fetal and neonatal alloimmune thrombocytopenia (AIT) is a serious disease that can affect subsequent siblings to an even greater degree than a first affected child. The devasting outcome of antenatal intracranial hemorrhage (ICH) is not uncommon. Great strides have been made in the antenatal diagnosis and treatment of this disease. This article reviews our knowledge of the laboratory diagnosis of AIT during pregnancy, the pitfalls in this diagnosis, the natural history of AIT during pregnancy, and the collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…7,22 In addition, serial fetal blood sampling and intra-uterine platelet transfusions may further sensitize the mother. 20,24 Finally, if maternal platelets are used in an intra-uterine transfusion, antiplatelet antibodies may be transfused into the fetus with the platelets. 20,25 Overall, as treatment results with maternal IVIG-based therapy have improved substantially 6,7,12,14,16 (Table 3), while the morbidity and mortality from fetal blood sampling remain considerable, the consensus at many centers at present is to minimize its use, and, if possible, to avoid fetal blood sampling completely.…”
Section: Financial and Other Disclosures Provided By The Authors Usinmentioning
confidence: 93%
See 3 more Smart Citations
“…7,22 In addition, serial fetal blood sampling and intra-uterine platelet transfusions may further sensitize the mother. 20,24 Finally, if maternal platelets are used in an intra-uterine transfusion, antiplatelet antibodies may be transfused into the fetus with the platelets. 20,25 Overall, as treatment results with maternal IVIG-based therapy have improved substantially 6,7,12,14,16 (Table 3), while the morbidity and mortality from fetal blood sampling remain considerable, the consensus at many centers at present is to minimize its use, and, if possible, to avoid fetal blood sampling completely.…”
Section: Financial and Other Disclosures Provided By The Authors Usinmentioning
confidence: 93%
“…20 A recent randomized study demonstrated that IVIG 1 g/kg/week alone does not work well in more severely affected patients (i.e., those with previous intracranial hemorrhage or whose initial fetal blood platelet count is £20¥10 9 /L). 12 Among patients treated in the standard-risk arm (platelet count at pre-treatment fetal blood sampling > 20¥10 9 /L and no history of intracranial hemorrhage in a previous sibling), less intensive therapy was appropriate and prednisone 0.5 mg/kg/day was as good as IVIG.…”
Section: Financial and Other Disclosures Provided By The Authors Usinmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of antenatal management in these series varied from 0 to 80% depending on the definition of response criteria. Bussel et al (48) observed a tendency towards higher responses in American than in European studies. When response is defined as a fetal platelet count >5Ox1Oy/1 at birth, 29 of the 57 infants (51%) responded.…”
Section: Neonatal Alloimmune Thrombocytopeniamentioning
confidence: 56%